Models for simulating the development of even-aged Pinus brutia stands in Middle East - de Miguel, Sergio; Pukkala, Timo; Shater, Zuheir; Assaf, Nabil; Kraid, Bassel; Palahí, Marc (Forest Systems, 2010)
Pinus brutia occurs in the Eastern Mediterranean region and is the most widespread conifer species in Middle East. It is important for multi-purpose forestry owing to its high ecological value and economic importance. To model the stand dynamics of P. brutia, 133 semi-permanent sample plots were placed in 10 to 166 year-old stands in Syria and Lebanon, covering the whole range of variation in site quality, stand age and stand density. Site index, distance-independent diameter increment, height and self-thinning models that included country effects were fitted to the data. The site index model was fitted using the guide curve method. The data for 10-year diameter growth model consisted of past growth measurements of all trees within the 133 plots. Diameter growth was modelled using variables representing site, size and competition. The self-thinning model was developed by estimating the maximum number of trees per hectare as a function of mean diameter and site index. These are the first cross-border models in Middle East enabling forest growth and yield predictions and stand dynamics simulations on an individual-tree basis. Such models will allow, with the aid of optimization techniques, finding the optimal forest management for P. brutia forests based on different management objectives.